Application of adaptive predictive Deconvolution in Marine Seismic Data - Si-xin Zhu; Bin Wang (Institute of Advanced Engineering and Science, 2014)
Aiming at reverberation and interlayer multiple short period common multiples, with predictive deconvolution multiple attenuation methods exist this problem several residues, through the design of adaptive filter, iterative formula of least mean square algorithm to update the adaptive predictor of key parameters of deconvolution, predictive step and factor by multiple wave length distribution period and different to automatically set the range. Through the model experiment, the method of reverberation, interlayer multiples were especially obvious effect data, and verified by practical data analysis maps, some key results contrast income, show that the method has a good application prospect.